Plan estratégico 2025-2029, para la procesadora de pollos J&B, Tumbabiro, Urcuqui, Imbabura. - Estrada Granja, Ana Nicole (2024)
The purpose of this study is the development of a 2025-2029 strategic plan for the J&B Chicken Processor, located in Tumbabiro, Urcuqui, province of Imbabura. A mixed approach was used, combining qualitative and quantitative methods. Surveys were conducted with 120 clients, 6 employees, interviews with the manager and the main supplier. A SWOT analysis was used for the strategic diagnosis and operational plans were developed for each strategic objective. The diagnosis revealed that the J&B Chicken Processor has significant strengths, including modern plants, trained and committed personnel, and its own distribution network. Customers recognize the high quality of the products. However, areas for improvement were identified in internal communication, infrastructure modernization and process optimization. A comprehensive strategic plan was developed that includes mission, vision, values, Quality policy, it is concluded that the proposed strategic plan provides a clear roadmap for the development of the Processor to significantly improve the competitiveness and performance of the company in the poultry market in the region, allowing it to achieve high quality standards and contribute to local economic development.